Water at the intersection of human rights and conflict: a case study of Palestine - Muratoglu, Abdullah; Wassar, Fatma (Frontiers in Water, 2024)
The global water crisis presents a multifaceted challenge intersecting with human rights and conflict, particularly evident in regions like Palestine. This study delves into the intricate dynamics of water scarcity in Palestine, with a specific focus on the Gaza Strip. The scarcity of water resources has a profound impact on agriculture and the economy, leading to increased food insecurity as a result of insufficient water availability for irrigation. Furthermore, the unequal distribution of water resources between Israel and Palestine perpetuates the crisis, with Israeli settlements consuming a disproportionate share compared to Palestinians. This research also highlights the widespread issue of water discrimination, where Israeli policies systematically restrict Palestinian access to water resources, thereby exacerbating existing disparities. In the Gaza Strip, the challenges are particularly severe, with a staggering 89% of the population lacking access to safely managed drinking water services. Addressing the water crisis in Palestine necessitates concerted efforts to enhance water security, safeguard water quality, and uphold the fundamental rights of the population. Collaborative initiatives are essential to alleviate the plight of communities in Gaza and across Palestine, ensuring equitable access to this vital resource and fostering sustainable development.